Energy Efficiency using Beamforming at the Base Station in UMTS and LTE - Gonçalves, Tiago (2018)
Trabalho apresentado em 20th International Conference on Software, Telecommunications and Computer Networks, 11-13 setembro 2012, Split, Croácia